2017
DOI: 10.1371/journal.pone.0172133
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of cold tolerance in rice (Oryza sativa) determined through high resolution genome-wide analysis

Abstract: Cold temperature is an important abiotic stress which negatively affects morphological development and seed production in rice (Oryza sativa L.). At the seedling stage, cold stress causes poor germination, seedling injury and poor stand establishment; and at the reproductive stage cold decreases seed yield. The Rice Diversity Panel 1 (RDP1) is a global collection of over 400 O. sativa accessions representing the five major subpopulations from the INDICA and JAPONICA varietal groups, with a genotypic dataset co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
115
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(124 citation statements)
references
References 75 publications
(109 reference statements)
9
115
0
Order By: Relevance
“…Wang et al (2016) identified 67 QTLs for cold tolerance at the seedling stage, and 56 of these QTLs were located in regions that had not been reported to contain cold tolerance-related QTLs. Shakiba et al (2017) identified 42 QTLs associated with cold tolerance at the seedling stage, 20 of which did not co-localize with previously reported cold-tolerant QTLs. Consequently, GWAS can identify new QTLs for cold tolerance and provide new insights into the genetic basis of cold tolerance in rice.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Wang et al (2016) identified 67 QTLs for cold tolerance at the seedling stage, and 56 of these QTLs were located in regions that had not been reported to contain cold tolerance-related QTLs. Shakiba et al (2017) identified 42 QTLs associated with cold tolerance at the seedling stage, 20 of which did not co-localize with previously reported cold-tolerant QTLs. Consequently, GWAS can identify new QTLs for cold tolerance and provide new insights into the genetic basis of cold tolerance in rice.…”
Section: Introductionmentioning
confidence: 57%
“…Most of these QTLs have been detected repeatedly using different bi-parental populations. Generally, japonica cultivars are more coldtolerant than indica cultivars (Shakiba et al 2017). Most bi-parental populations used in QTL analyses have been derived from a cross between a cold-tolerant japonica variety and a cold-sensitive indica variety; consequently, most QTLs associated with cold tolerance are derived from the japonica parent (Andaya and Mackill 2003;Kuroki et al 2007;Ma et al 2015;Zhu et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…At the germination stage, GWAS mapping of a collection of 63 rice varieties from Hokkaido, Japan identified 17 QTL (Fujino et al, 2015) and evaluation of the Rice Diversity Panel 1 (RDP1) revealed a total of 42 QTL (Shakiba et al, 2017). RDP1 seedlings at the three-leaf stage, were subjected to 3 days of chilling treatment, scored for chilling survivability and GWAS mapping revealed 67 QTL located on 11 chromosomes (Wang et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…The challenge of global warming means that crop plants, including rice, will be more exposed to extreme growing environments, e.g., low and high temperatures. Although the response by rice to cold stress has been described (Zhi-guo et al, 2014; Wang D. et al, 2016; Shakiba et al, 2017), we still need to identify more effective genes that can regulate this response.…”
Section: Introductionmentioning
confidence: 99%